Implementation of the scenario simulation teaching method in the clinical teaching practice of oral medicine for nursing students (情景模拟教学法在口腔内科护生临床教学实践中的应用效果) - MA Yuan (马嫄); MA Tao (马涛); MAO Yaxun (毛雅洵); WANG Xiaoyan (王晓燕); LIU Sha (刘莎) (中西医结合护理, 2024)
Objective To explore the implementation effect of scenario simulation teaching method in the clinical teaching practice of oral medicine for nursing students. Methods A total of 68 nursing students who participated in clinical internship were selected, all of whom are full-time students majoring in oral nursing. Nursing students with internship between January 2021to December 2021 were allocated into the control group, receiving a routine teaching method during clinical practice. Nursing students with internship from January 2022 to December 2022 were included as the study group, receiving the scenario simulation teaching method. To investigate nursing students' knowledge and practices of oral care, and to evaluate their satisfaction with clinical teaching environment. Results The comprehensive test score of the nursing students in the study group (94. 51±5. 02) was higher than that of the control group (89. 32±5. 93), with a significant difference (P＜0. 05). In terms of the clinical environment practice evaluation, the study group achieved higher scores than the control group in aspects of teaching methods, learning opportunities, and organizational support, and the results were statistically different (P＜0. 05). Conclusion Scenario simulation teaching improves the clinical theoretical knowledge and clinical practice level of oral medicine nursing students, and also improves the satisfaction of nursing students with clinical practice environment. (目的 探讨情景模拟教学法在口腔内科护生临床教学实践中的应用效果。方法 选取2021年1月—12月北京大学口腔医院牙体牙髓科实习的34名护生为对照组, 另选取2022年1月—12月实习的34名护生为研究组。对照组实施口腔内科常规临床护理教学法, 研究组实施情景模拟教学法。分别于入科时和出科前对两组护生进行理论与操作考核, 比较两组对临床学习环境的满意度。结果 两组出科考试成绩均高于入科时, 研究组护生综合考试成绩(94. 51±5. 02)分, 高于对照组的(89. 32±5. 93)分, 差异有统计学差异(P＜0. 05)。研究组护生对教学方法、学习机会、组织支持维度的临床学习环境评价满意度高于对照组, 差异有统计学意义(P＜0. 05)。结论 情景模拟教学不仅有助于提高口腔内科护生临床理论知识和临床操作水平, 且临床学习环境更好, 起到了教学相长的作用, 值得推广应用。)